Tinjauan Aspek Hukum Terhadap Perlindungan Bagi Konsumen dalam Transaksi Jual Beli Online(E-Commerce) - Julitta Dewayani; Sri Heneng Prasastono; Heni Dwi Listyaningrum; Galuh Aditya; Henny Kumalasari Widodo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Differences in Results Regarding Legal Protection for Consumers When Carrying Out Online Buying and Selling Transactions. Identify legal protection for customers during e-commerce transactions based on UUPK. 2. Identify legal protection for customers during UUITE e-commerce transactions. This research was conducted to determine the legal aspects of legal protection for consumers when carrying out online buying and selling transactions. Normative juridical research methodology, also known as library research. Both UUPK and UUITE have not been fully implemented to regulate electronic buying and selling transactions. Many consumers still do not receive their rights when they become victims of errors in online buying and selling transactions. The main factors that make it difficult for consumers to obtain legal protection from relevant authorities are also influenced by a lack of socialization and consumer understanding. With current technological advances, it is hoped that businesses, consumers and related bodies will be more aware of better legal protection for all parties.